Analisis Perbandingan Terhadap Hasil Belajar PAI Mahasiswa Lulusan Madrasah Aliyah Dan Sekolah Umum - Sri Ihwani; Adiyana Adam; Asmawati Harun; Nursahna D. Hi. Yahya (Peneliti.net, 2023)
The veil is a piece of cloth used by Muslim women to cover their genitals, especially on the face. The law on the use of the veil also varies, some are mandatory and some are sunnah. Nowadays, the veil is often misused for the sake of certain interests so as to make the good image of people who wear the veil bad, what was originally seen as good by society is now seen as bad as terrorists and so on. Therefore, the presence of this article is one of the efforts to make the public aware so that they are not consumed by the spread of hoaxes that have hit the community, namely people wearing veils are terrorists. This study uses qualitative research in the form of observations on PAI students at IAIN Ternate, especially in semester 5.